HEAVY METAL POLLUTION IN SURFACE WATER AND SEDIMENT: A PRELIMINARY ASSESSMENT OF THAMIRABARANI RIVER IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The concentration and toxicity of five heavy metals (Cu, Zn, Cd, Ni and Pb) were measured in surface water and sediment of Thamirabarani river in Kanyakumari district, Tamilnadu, India. The present study was carried out the analysis of heavy metals in Thamirabarani river fromPechiparai Dam to Thengaipattinam estuary during the period from September 2020 to August 2021. The decreasing trend of metals were observed in water as Pb > Ni > Zn > Cd > Cu and in sediment as Zn > Cu > Pb > Ni > Cd. The value of studied metals exceeded the safe limits of drinking water, indicating that water from this river is not safe for domestic purposes. Total concentrations of Cd and Pb in the water samples were higher than WHO guidelines for drinking water quality for a maximum number of stations. Enrichment factor (EF), Contamination factor (CF) and Potential ecological risk index (Eri) revealed high values of cadmium in the Thamrabarani river.